SKRINING DAN UJI DIAGNOSTIK COVID-19 DI PUSKESMAS DEPOK III SLEMAN, DAERAH ISTIMEWA YOGYAKARTA - Liena Sofiana; Nindy Fadellah Wulan Safitri; Trisno Agung Wibowo (Universitas Ahmad Dahlan, 2022)
Coronavirus Disease 2019 (COVID-19) is a communicable disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Transmission of SARS-CoV-2 virus mainly through close contact and droplets. Common symptoms of COVID-19 infection include acute respiratory symptoms such as fever, cough, and dyspnea. If the discovery of COVID-19 cases is not fast can increase the potential spread of the disease widely and also increase the severity of the disease in the form of ARDS until death. The purpose of this study is to determine sensitivity, specificity, positive predictive value (NPP), negative predictive value (NPN) and different proportion of symptoms of COVID-19 disease with RT-PCR checks in Puskesmas Depok III Sleman, Special Region of Yogyakarta.This type of research is descriptive with quantitative approach. The sampling technique used total sampling with 399 samples. Data were analyzed using descriptive analysis into the form of tables and narratives. The sensitivity value of seven symptoms of COVID-19 in this study was under the desirable value (≥99%) acceptable value (≥97%). The symptoms of COVID-19 in this study cannot be used for COVID-19 screening in Puskesmas Depok III Sleman, Special Region of Yogyakarta.